Optimalisasi E-Commerce untuk Pemberdayaan Budidaya Lele UMKM dan Karang Taruna di Semarang - Amsar Amsar; Camilus Isidorus Ikut; Rr. Suprantiningrum (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Empowering catfish cultivation has great potential to improve community welfare, especially for Micro, Small, and Medium Enterprises (MSMEs) and Karang Taruna groups. This program aims to optimize local resources in Pesantren Village, Mijen District, Semarang City, through training in sustainable catfish cultivation. The methods used include technical training, mentoring, and providing initial facilities. The use of e-commerce in Empowering of catfish cultivation is expected to have a positive impact, both economically and socially.